Problematika Kependudukan Indonesia - Mu’awwanah, Uliyatul; Ridho Illah, Ghoni Rizky (INAIFAS Press, 2022)
The increase in population does not necessarily become a good sign if it is not balanced with an increase in welfare. Welfare also is not necessarily only seen from how much income is earned. However, it also covers more essential aspects such as the economy, education, and health. The rate of population growth is the increase in the number of people caused by the explosion in the birth rate. Indonesia is a country that has a fairly high birth rate. In addition, Indonesia is also one of the countries with the highest population in the world. From the discussion on population, it appears that there are problems with a population including the problem of birth rates, life expectancy, population numbers, and population density problems. To overcome or minimize these problems, the government, especially in Indonesia, needs special attention to various strategies or the right way to overcome them in the hope that the right strategy will be able to help making the economy in Indonesia even better. This paper seeks to contribute to literacy for readers in particular and the Indonesian population in general so that they are expected to be able to identify the problems experienced for the sake of Indonesia’s target of becoming a developed country by starting with self-development. In other words, welfare development does not only start when a person can work, but goes further than that, namely since the individual is in his/her mother’s womb.